2010
DOI: 10.1242/dev.047324
|View full text |Cite
|
Sign up to set email alerts
|

Developmental RNA processing of 3′UTRs in Hox mRNAs as a context-dependent mechanism modulating visibility to microRNAs

Abstract: SUMMARYThe Drosophila Hox gene Ultrabithorax (Ubx) controls the development of thoracic and abdominal segments, allocating segmentspecific features to different cell lineages. Recent studies have shown that Ubx expression is post-transcriptionally regulated by two microRNAs (miRNAs), miR-iab4 and miR-iab8, acting on target sites located in the 3Ј untranslated regions (UTRs) of Ubx mRNAs. Here, we show that during embryonic development Ubx produces mRNAs with variable 3ЈUTRs in different regions of the embryo. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
68
0
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(73 citation statements)
references
References 46 publications
(78 reference statements)
2
68
0
3
Order By: Relevance
“…In addition, HOX loci are known to host at least three miRNA genes (Lagos-Quintana et al 2001;Bender 2008;Stark et al 2008;Tyler et al 2008), one of which was previously shown to be regulated by Polycomb (Ronshaugen et al 2005). Among the suspected targets are the HOX genes themselves (Stark et al 2008;Tyler et al 2008;Thomsen et al 2010), thus providing an opportunity for direct regulatory feedback. Another interesting aspect is the novel connection to important growth-regulating miRNAs such as bantam and mir-8, in line with known PcG targets in cell cycle control (Martinez et al 2006;Oktaba et al 2008).…”
Section: Prc1 Binds Promoters Of Coding and Noncoding Genesmentioning
confidence: 99%
“…In addition, HOX loci are known to host at least three miRNA genes (Lagos-Quintana et al 2001;Bender 2008;Stark et al 2008;Tyler et al 2008), one of which was previously shown to be regulated by Polycomb (Ronshaugen et al 2005). Among the suspected targets are the HOX genes themselves (Stark et al 2008;Tyler et al 2008;Thomsen et al 2010), thus providing an opportunity for direct regulatory feedback. Another interesting aspect is the novel connection to important growth-regulating miRNAs such as bantam and mir-8, in line with known PcG targets in cell cycle control (Martinez et al 2006;Oktaba et al 2008).…”
Section: Prc1 Binds Promoters Of Coding and Noncoding Genesmentioning
confidence: 99%
“…36 Like polo, ubx mRNAs contain target sites for miRNAs, however the differential expression of the two ubx mRNAs is not due to miRNA silencing but to alternative polyadenylation. Additionally, the longer ubx isoform is not upregulated in proliferation deficient string mutants, suggesting that proliferation is not the driving-force behind ubx alternative polyadenylation.…”
Section: A Role For Polo Alternative Polyadenylation In Metamorphosismentioning
confidence: 99%
“…Previous work in our laboratory focused on the mechanisms and impact of RNA regulation on the expression and neural function of the Drosophila Hox genes (3)(4)(5)(6). These genes encode a family of evolutionarily conserved transcription factors that control specific programs of neural differentiation along the body axis (7)(8)(9) offering an opportunity to investigate how RNA regulation relates to the formation of complex tissues such as the nervous system.…”
mentioning
confidence: 99%
“…Here we use the Hox gene system to investigate the roles played by a single miRNA locus (miR-iab4/8) (3,(10)(11)(12)(13)(14)30) on the specification of the nervous system during early Drosophila development. This miRNA locus controls the embryonic expression of posterior Hox genes (3,(10)(11)(12)(13)(14).…”
mentioning
confidence: 99%
See 1 more Smart Citation